Implementation of Moral Sufism in Islamic Religious Education - Samsudin (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
Sufism is a field of study in Islamic studies that has been researched from time to time and has developed rapidly, becoming a scientific discipline that is closely related to efforts to improve morals in people's lives through Islamic Religious Education (PAI). In other words, Sufism is not only an effort to purify oneself individually but also helps build a society with noble morals by drawing closer to Allah as Al-Khaliq. 'rifatullah. Moral Sufism is one method of studying Sufism. Moral Sufism is Sufism that upholds moral development. To achieve moral perfection or insan kamil, the teachings of moral Sufism really emphasize amaliyah-amaliyah or purity of soul which relies on strengthening mental attitudes and strict behavioral discipline through the practice of istiqomah (riyadhoh). Bearing in mind the current condition of modern society which is characterized by decadence and moral crisis caused by a liberal lifestyle and hedonism, the moral teachings of Sufism are very important to convey in an effort to improve social and individual order in everyday life